10.1111/acn.v9999.9999 (CrossRef Listing of Deleted DOIs, 2000)
Although osteosarcoma is the most common primary bone tumour in dogs, involvement of the pelvic bones is rare. The aim of the present study was to describe clinical presentation, identify possible prognostic factors, and evaluate outcomes in dogs diagnosed with pelvic osteosarcoma. Seventy-four dogs with cytologically or histologically diagnosed pelvic osteosarcoma were included in this multicentre retrospective study (2007-2025). The median progression-free survival (PFS) and overall survival (OS) were estimated using the Kaplan-Meier method, with comparisons performed using log-rank tests. Prognostic factors for PFS and OS were assessed using multivariable Cox proportional hazards regression analysis. Lameness (84%) was the most common presenting clinical sign, and the ilium (57%) was the most frequent intrapelvic tumour location. Thirty-one percent of dogs had metastases at diagnosis, primarily affecting the lungs. The median PFS was 75 days, and the median OS was 79 days. Dogs receiving any treatment had significantly longer PFS (116 vs. 7 days, p < 0.001) and OS (145 vs. 8 days, p < 0.001) than untreated dogs. No factors were significantly associated with PFS. In contrast, dogs with higher body weight and shorter time to diagnosis tended to have more favourable survival, whereas chemotherapy and local progression were associated with poorer outcomes. Despite the overall poor prognosis associated with pelvic osteosarcoma, treatment may extend survival. An individualized, often multimodal approach may provide clinical benefit in selected dogs.